2019
DOI: 10.1111/his.13835
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of lysosomal protective protein (cathepsin A) in breast ductal carcinoma in situ

Abstract: Aims Cathepsin A (CTSA) is a key regulatory enzyme for galactoside metabolism. Additionally, it has a distinct proteolytic activity and plays a role in tumour progression. CTSA is differentially expressed at the mRNA level between breast ductal carcinoma in situ (DCIS) and invasive breast carcinoma (IBC). In this study, we aimed to characterise CTSA protein expression in DCIS and evaluate its prognostic significance. Methods and results A large cohort of DCIS [n = 776 for pure DCIS and n = 239 for DCIS associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
2
23
0
1
Order By: Relevance
“…Similar to our findings, low expression of IGF2R in nonsmall cell liver cancer has been associated with poor prognosis and high expression in bladder cancer has been associated with good prognosis [57,58]. Although high CTSA expression was associated with poorer outcome in breast ductal carcinoma in situ, it was also found to suppress invasion and metastasis of colorectal cancer, suggesting tissue-specific differential roles [59,60]. Recent studies linked ATP6AP2 up-regulation to the progression of glioma and colorectal cancer, due to its roles in aberrant activation of the Wnt/beta-catenin signalling pathway [61,62].…”
Section: Discussionsupporting
confidence: 83%
“…Similar to our findings, low expression of IGF2R in nonsmall cell liver cancer has been associated with poor prognosis and high expression in bladder cancer has been associated with good prognosis [57,58]. Although high CTSA expression was associated with poorer outcome in breast ductal carcinoma in situ, it was also found to suppress invasion and metastasis of colorectal cancer, suggesting tissue-specific differential roles [59,60]. Recent studies linked ATP6AP2 up-regulation to the progression of glioma and colorectal cancer, due to its roles in aberrant activation of the Wnt/beta-catenin signalling pathway [61,62].…”
Section: Discussionsupporting
confidence: 83%
“…Among the many potential biomarkers, such as genetic, immunological, and haematological markers, systemic inflammatory markers in peripheral blood are receiving increasing attention for prediction of tumour recurrence, metastasis, and prognosis [1618]. Recent studies have shown that absolute inflammatory cell counts in peripheral blood (neutrophils, white blood cells, lymphocytes and monocytes) and ratios based on these cell counts (NLR, PLR and LMR) may play a key role in predicting the overall survival of patients with tumours, including colorectal cancer [19], head and neck cancer [20], non-small cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin A (CTSA) is a renowned serine protease cathepsin member of the cathepsin lysosomal protease family, which with a role in protecting β-galactosidase and neuraminidase-1 from intra-lysosomal proteolysis 19 . In recent years, CTSA overexpression has been observed in various types of human cancers such as breast cancer, lung cancer, and prostate cancer 20 23 . CTSA also has been identified as a potential biomarker for early diagnosis, prognosis and monitoring during cancer treatment.…”
Section: Introductionmentioning
confidence: 99%